Book of abstracts of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017 (International Table Tennis Federation, 2017)
Gunter Straub OVTCHAROV AGAINST THE BIG FOUR - AN ANALYSIS OF THE PLAYING STYLE OF EUROPE´S NUMBER ONE IN TABLE TENNIS: RESULTS OF THREE-PHASE DIAGNOSTICS 12 Diana Zerdila, Ioannis Kordoutis, Stella Rokka, Giorgos Mavridis, Aikaterini Papadimitriou LEADERSHIP BEHAVIOUR AND SATISFACTION IN YOUNG TABLE TENNIS PLAYERS 12 Valérian Cece, Guillaume Martinent, Marije Elferink-Gemser, Irene R. Faber, Jean-Claude Decret THE ROLE OF PSYCHOLOGICAL FACTORS IN TALENT DEVELOPMENT AMONG YOUTH TABLE-TENNIS PLAYERS INVOLVED IN INTENSIVE TRAINING PROGRAMS 13 Jennifer G. Inovero, Fernando P. Florendo MODIFIED TABLE TENNIS FOR A VISUALLY IMPAIRED MALE COLLEGE STUDENT: A CASE STUDY 13 Higinio González-García, Antonia Pelegrín Muñoz MENTAL ABILITY DIFFERENCES IN TABLE TENNIS PLAYERS DEPENDING ON AGE 14 Mahmoud Ghuneim STUDY FOR THE POSSIBILITIES AND HURDLES ENCOUNTERED WITH COACHING ONE JUNIOR AND/OR YOUTH PLAYER SWITCHING STYLES FROM CLASSICAL SHAKE HAND STYLE TO NEW "MG-SHIP" STYLE 14 Mohammad Reza Sadeghian Shahi, Rosa Rahavi Ezabadi, Najmeh Abootalebi, Parisa Moshiri THE EFFECTS OF THE SELF-TALK TYPES AND TASK COMPLEXITY ON THE ACCURACY OF FOREHAND TOP SPIN OF ADVANCED PLAYERS 15 Ralf Schneider, Karl Felix Lüskow, Stefan Kemnitz STUDIES OF THE INFLUENCE OF BALL SIZE AND NET HEIGHT ON TABLE TENNIS TRAJECTORY DISTRIBUTIONS 15 Ching-Yi Sung, Chyong-Huoy Huang, Yu-Fen Chen TECHNICAL ANALYSIS OF THE 2016 RIO OLYMPIC GAMES WOMEN`S SINGLE TABLE TENNIS CHAMPIONSHIP COMPETITION 16 Chyong-Huoy Huang, Ching-Yi Sung CASE STUDY OF NATIONAL KAOHSIUNG UNIVERSITY OF APPLIED SCIENCES` STUDENTS INTEREST IN LEISURE SPORTS WHOM HAD TAKEN TABLE TENNIS COURSES 16 Ming-Hua Hsu, Yu-Fen Chen, Tz-Chung Chou DEVELOPING OF A FLIPPED CLASSROOM LEARNING SATISFACTION SCALE ON UNIVERSITY TABLE TENNIS PROGRAM 17 Xianyi Zou THE STUDY OF CHINESE TABLE TENNIS CROSS-CULTURAL TRANSMISSION BASING ON THE STRATEGY OF "THE BELT AND ROAD" 17 Willian Gabriel Felício da Silva, Fábio Tadeu Reina ANALYSIS OF THE DURATION RALLY AND REST TIME OF WHEELCHAIR PARA TABLE TENNIS AT THE RIO 2016 PARALIMPIC GAMES 18 Emilio Sulis, Rosa Meo, Rossano Schifanella, Antonio Arisi A NETWORK ANALYSIS OF TABLE TENNIS MATCHES PLAYED IN ITALY 18 Taotao Zhang, Wencheng Wang THE STUDY ON NURTURING TERTIARY STUDENTS AS DOCTOR FOR UNIVERSITY SPORTS TEAM IN MEDICAL UNIVERSITY - A CASE STUDY ON TABLE TENNIS TEAM OF DALIAN MEDICAL UNIVERSITY 19 Ming-Kun Chen, Pei-Chan Chin, Tz-Chung Chou STUDY OF NATIONAL GAMES` TABLE TENNIS TAINAN MEN TEAM 22 PEAT DEVELOPMENT COURSE (1984 - 2011) 19 Ping Gao, Yukihiko Ushiyama, Junichi Hori, Rei Akagawa, Akiyoshi Shioiri, Kei Kamijima, Yuumi Terada ANALYSIS OF MENTAL STATE OF ATHLETES UNDER PRESSURE USING ELECTROENCEPHALOGRAPH(EEG) 20 Xinrong Li, Zhongliang Liu THE THINKING OF TABLE-TENNIS` GLOBALIZATION DEVELOPMENT 20 Haoyu Liu, Xianfeng Wu THE CURRENT SITUATION AND THE DEVELOPMENT PROSPECT OF PUBLIC TABLE TENNIS RATING GAME IN CHINA 21 Jan Haut DOES ELITE SUCCESS HELP TO PROMOTE PARTICIPATION IN TABLE TENNIS? A LONG-TERM ANALYSIS OF TRICKLE-OWN EFFECTS IN GERMANY, FRANCE AND AUSTRIA 21 Xiaodong Zhang, Dandan Xiao, Yingqiu Zhang THE TECHNICAL AND TACTICAL ANALYSIS ON MA LONG VS MIZUTANI JUN IN SEMI-FINAL MATCH AT 2016 OLYMPIC GAME 22 Chi Chiu Hung, Wen Bin Lin, Sau Chu Chan, Kim Fong Yuen OUR EFFORTS TO SAVE THE FUTURE OF PEN-HOLD GRIP . DISCUSSION ON THE FUTURE DEVELOPMENT OF PEN-HOLD GRIP IN TABLE TENNIS 22 Jie Wang COMPARISON OF GAME CHARACTERISTICS OF LONDON (2012) AND RIO (2016) OLYMPIC TABLE TENNIS GAMES 23 Jiacheng Feng, Jing Chen NONCONVENTIONAL TECHNIQUES ANALYSIS FOR ALL-ROUND ATTACK IN TABLE TENNIS 23 Chia-Jung Lin, Chiu-Ju Lu THE INFLUENCE OF LEISURE MOTIVATION AND EXERCISE INVOLVEMENT ON EXERCISE HABIT 24 Yang Yu, Guozheng Liu RESEARCH ON PREPARATION MODE FOR INTERNATIONAL MATCH OF CHINA NATIONAL MAN 'S JUNIOR TABLE TENNIS TEAM 24 Shuang Hou, Jie Ren RESEARCH ON RESPONSE INHIBITION OF TABLE TENNIS PLAYERS WITH DIFFERENT LEVELS 25 Jie Ren, Yue Lu THE EVALUATION OF ANTICIPATION ABILITY FOR TABLE TENNIS PLAYER: BASED ON HICK'fS LAW 25 Jonathan Glynn CASE STUDY: USING VIDEO ANALYSIS OF MATCHES TO TRACK PLAYER PERFORMANCE AND INFORM TRAINING 26 Junwei Xu, Hongxia Li, Wenxia Guo RESEARCH ON SCORING CHARACTERISTIC, CAUSES AND DEVELOPMENT OF TECHNICAL AND TACTICAL APPLICATION IN COMPETITION OF MALE ATHLETES IN NEW ERA 26 Jo.ko Sindik, Michael Fuchs, Martin Lames, Tina Matja.i., Miran Kondri. DIFFERENCES IN MATCH STATISTICS DURING TABLE TENNIS TEAM EVENT IN RIO AND LONDON OLYMPIC GAMES 27 Chung-Yi Wang Li, Ju-Ping Chou, Li Chuan Wu EFFECT OF DIFFERENT SHAKE-HAND GRIP ON BACKHAND "CHIQUITA" VELOCITY 27 Andreas Mierau, Thorben Hulsdunker, Heiko K. Struder BRAIN PROCESSES ASSOCIATED WITH FASTER VISUOMOTOR REACTION TIME IN RACQUET SPORT ATHLETES 28 Xinrong Li, Zhongliang Liu THE DISCUSSION ABOUT TABLE TENNIS' DEVELOPMENT IN CHINA AND WORLD 28 Oscar Yoshihiro Santelices, Arnulfo Lopez COMPETITIVE READINESS OF MALE AND FEMALE TABLE TENNIS ATHLETES OF THE UNIVERSITY OF THE PHILIPPINES: BASIS FOR A PROPOSED INTERVENTION TRAINING PROGRAM 29 Hai Wang AN ANALYSIS ON SOCIAL VALUE AND FUNCTION OF SPORTS OF TABLE TENNIS IN THE WORLD FROM THE PERSPECTIVES OF EDUCATION, POLITICS, ECONOMY AND CULTURE 29 Michail Katsikadelis, Theophilos Pilianidis, Nikolaos MantzƒÍuranis, Ioannis Fatouros, Nikolaos Agelousis THE EFFECT OF DETRAINING ON CARDIOVASCULAR RESPONSES IN YOUNG TABLE TENNIS PLAYERS 30 Ivana Nikoli., Gordana Furjan Mandi., Miran Kondri. FACTOR STRUCTURE OF MORPHOLOGICAL AND MOTOR CHARACTERISTICS OF A YOUNG TABLE TENNIS PLAYERS 30 Sepideh Mohammadkhan Beigi, Fatemeh Keyvani THE EFFECT OF ISOTONIC RESISTANCE TRAINING ON INTERLEUKIN 6 IN FEMALE TABLE TENNIS PLAYERS 31 Michiyo Kimura, Maimi Maruyama, Mizuho Adachi, Naomi Iino, Megumi Ooishi FACTORS ASSOCIATED WITH GOOD FOOD AWARENESS AND BEHAVIORS IN JAPANESE CADET TABLE TENNIS PLAYERS 31 Larissa Rafaela Galatti, Caio Corrêa Cortela, Willian Gabriel Felício da Silva, Milton Shoiti Misuta, Taisa Belli THEORETICAL AND PRACTICAL KNOWLEDGE FOR TABLE TENNIS COACHES DEVELOPMENT IN A SPORTS SCIENCE BACHELOR`S DEGREE 32 Chi-Yueh Hsu, Hsiu-Jung Hsieh, Pei-Ting Chang RESEARCH ON TECHNIQUES AND TACTICS OF DIFFERENT GRIP TYPES USED BY TABLE TENNIS PLAYERS 32 Maryam Abdoshahi, Sima Limoochi THE COMPARISON OF AROUSAL, ANXIETY AND SELF-CONFIDENCE BETWEEN IRANIAN WOMEN AND MEN ELITE TABLE TENNIS PLAYERS 33 Manfred Muster ABOUT THE IMPORTANCE OF "SITUATIONAL TRAINING" IN HIGH PERFORMANCE TABLE TENNIS - EMPIRICAL STUDY AIMING TO IDENTIFY MATCH SITUATIONS 33 Samuel Pullinger, Marco Cardinale, Abdallah Rejeb TRAINING LOAD AND INJURY INCIDENCE IN YOUTH TABLE TENNIS PLAYERS 34 Zhan Li, Ruizhi Liu ANALYSIS OF TECHNIQUE AND TACTIC FEATURE OF CHINESE EXCELLENT FEMALE TABLE TENNIS PLAYER - LIU SHIWEN 34 Ruizhi Liu THE COMPARATIVE RESEARCH ON THE FEATURES OF MATCH AND TRAINING FOR MAIN PLAYERS OF CHINA TABLE TENNIS FEMALE TEAM — BASED ON CELLULOID AND PLASTIC BALLS 35 Yoshinori Takeuchi, Kazuto Yoshida BOUND POSITION AND HITTING TIME ESTIMATION BY USING MICROPHONES EQUIPPED AT A TABLE IN TABLE TENNIS 35 Zhenhu Wang, Ruizhi Liu ANALYSIS OF THE SUCCESSFUL EXPERIENCE OF CHINA TABLE TENNIS TEAM FROM THE VICTORY OF RIO OLYMPIC GAMES IN 2016 36 Ana Isabel de la Torre, Francisco Pradas, Pau Salvà, Carlos Castellar, Jose Antonio González-Jurado ANALYSIS OF ANTHROPOMETRIC MODIFICATIONS IN YOUNG PLAYERS DERIVED FROM PRACTISING TABLE TENNIS 36 Yu-Fen Chen, Chen-Chih Huang A STUDY OF STUDENTS MOTIVATIONS AND FLOW EXPERIENCE ON PARTICIPATING TABLE TENNIS 37 Wenxia Guo, Junwei Xu, Dandan Xiao A COMPARATIVE STUDY OF CHINESE AND FOREIGN ELITE MALE TABLE TENNIS PLAYERS' ABILITY TO GRASP "KEY POINTS" 37 Lingfen Tang RESEARCH ON THE DEVELOPMENTAL DILEMMAS AND COUNTERMEASURES OF CHINESE AND FOREIGN TABLE TENNIS 38 Xinwen Li, Christine A. Rochester, Qing Chen, Bin Yuan THE MOBILITY OF SPORTS COMMUNICATION - THE STUDY ABOUT MOBILE NEWS CLIENTS APPLY IN THE TABLE TENNIS TOURNAMENT 38 Oscar Yoshihiro Santelices, Francis Carlos Diaz ANTHROPOMETRIC PROFILE OF THE UNIVERSITY OF THE PHILIPPINESTABLE TENNIS STUDENT-ATHLETES: BASIS IN DESIGNING COMPREHENSIVE INTERVENTION PROGRAMS 39 Willian Gabriel Felício da Silva, Fábio Tadeu Reina ANALYSIS OF THE DURATION OF RALLY AND REST TIME IN STANDING PARA TABLE TENNIS OFFICIAL TOURNAMENTS 39 Neil Patrick Ferrer, Oscar Yoshihiro Santelices, Mona Liza Maghanoy, Christian Wisdom Valleser COMPARATIVE ANALYSIS OF THE TABLE TENNIS PLASTIC BALL AND CELLULOID BALL IN TERMS OF RACKET ANGLE 40 Zheng Dai, Yan Wang AN ANALYSIS OF THE TYPE OF PLAY OF THE WORLD`S BEST YOUNG TABLE TENNIS PLAYERS - WORLD JUNIOR TABLE TENNIS CHALLENGE 2016 40 Jiamin Zhang, Jie Ren THE FRAMING EFFECT ON TACTICAL DECISION MAKING OF HIGH LEVEL TABLE TENNIS PLAYERS UNDER PSYCHOLOGICAL PRESSURE 41 Kei Kamijima, Kenichi Itoh, Yukihiko Ushiyama, Akiyoshi Shioiri, Ping Gao, Yuumi Terada A METHOD OF ESTIMATING BALL DROP AREA USING AE MEASUREMENT 41 Ivan Malagoli Lanzoni, Marco Farina, Irene Nardella, Silvia Fantozzi KINEMATIC ANALYSIS OF TOP SPIN FOREHAND WITH CELLULOID AND PLASTIC BALL 42 Ivan Malagoli Lanzoni, Rocco Di Michele NOTATIONAL ANALYSIS IN TOP-LEVEL TABLE TENNIS: A CASE STUDY 42 Ivan Malagoli Lanzoni, Rocco Di Michele, Gabriele Semprini FIFTY YEARS OF TOP-CLASS TABLE TENNIS WORLD RANKING 43 Ju Li, Suchuan Dai, Lei Ma STRESS REDUCED THE CAPACITY OF ATTENTION RESPONSES REGULATION OF AMATEUR BUT NOT TABLE TENNIS ATHLETES 43 Sho Tamaki DEVELOPMENT A COMPUTER PROGRAM FOR SPATIAL-TEMPORAL ANALYSIS OF TABLE TENNIS 44 Rizal Wan, Jia Yi Chow, Robert Rein UNDERSTANDING HYSTERESIS IN DISCRETE MULTI-ARTICULAR ACTION PERFORMED BY SKILLED AND NOVICE TABLE TENNIS PLAYERS 44 Zoran Djoki., Goran Munivrana, Dragomir Levajac MATCH CHARACTERISTICS OF PROFESSIONAL EUROPEAN MALE TABLE TENNIS PLAYERS 45 Angelita Cruz, Oscar Yoshihiro Santelices BLOOD PRESSURE RESPONSE TO EXERCISE IN TABLE TENNIS VARSITY ATHLETES 45 Rizal Wan, Jia Yi Chow, Robert Rein PERTURBATION INDUCED TASKS TO DICHOTOMISE SKILL LEVELS 46 Chiu-Ju Lu, Tung-Hsien Fang, Mei-Yao Huang, Wei-Chu Chang THE EFFECTS OF SOCIAL LOAFING ON TABLE TENNIS: THE MODERATING EFFECT OF PEER LEADERSHIP AND SPORT CONFIDENCE 47 Yingqiu Zhang and Dandan Xiao THE EFFECT OF RULES REFORM ON THE TECHNIQUES AND TACTICS OF TABLE TENNIS 47 Paul Ellison, Andy S. Sparks, Philip Murphy, David Marchant THE IMPACT OF AN EYE-HAND COORDINATION INTERVENTION ON THE DOMINANT HAND IN EXPERIENCED TABLE TENNIS PLAYERS 48 Alejandro Quintas, Francisco Pradas, Pau Salva, Ana de la Torre, Jose Antonio Gonzalez-Jurado, Carlos Castellar TABLE TENNIS PREVALENCE IN PRIMARY SCHOOLS OF ZARAGOZA (SPAIN) 48 Zoran Djokic Goran Munivrana, Dragomir Levajac ANTHROPOMETRIC CHARACTERISTICS OF TOP-CLASS WORLD AND EUROPEAN MALE TABLE TENNIS PLAYERS 49 Srban Dobo.i, Paula Apostu, Nicolae Ochian. THE EFFECT OF GLUCOSE SUPPLEMENTS ON EXERCISE CAPACITY IN TABLE TENNIS PLAYERS 49 Zoran Djoki., Goran Munivrana, Dragomir Levajac ROLE OF SERVE AND RETURN OF SERVE AT EUROPEAN GAMES 2015 TABLE TENNIS TOURNAMENT 50 Yi Sun, Mei-Lian Sun, Ming-Yueh Wang A STUDY OF MOTION ABOUT TABLE TENNIS' STEP' AND CROSS STEPs 50 Yuumi Terada, Yukihiko Ushiyama, Kei Kamijima, Akiyoshi Shioiri, Ping Gao DEVELOPMENT OF A SYSTEM TO ANALYZE THE COURSE PATTERN OF BALL USING SOUND SENSOR IN TABLE TENNIS COMPETITION 51 Hsiu-Hui Chiang, Chi-Yueh Hsu, Kuei-Lan Tsai A STUDY ON THE RELATIONSHIP OF INFLUENCE OF ATTITUDE, TRUST, PERCEIVED RISK AND INTENTION OF INVESTMENT IN ONLINE CROWDFUNDING OF TABLE TENNIS ENTHUSIASTS 51 Irene R. Faber, Johan Pion, Bas Willemse, Willianne Schipper, Maria W.G. Nijhuis-Van der Sanden EYE-HAND COORDINATION AND EXECUTIVE FUNCTIONS AS DETERMINANTS FOR PERFORMANCE IN ELITE AND NON-ELITE PARA TABLE TENNIS PLAYERS 52 Derek Han-Chieh Yang, Pei-Ting Chang, Hsing-Lee Lin A STUDY ON THE EFFECT OF SERVICE FAILURE, COMPENSATION TOWARD CONSUME AGAIN OF TABLE TENNIS CLUB 52 Adrian Alexandru Mosoi MOTIVATIONAL CHARACTERISTICS IN RACKET SPORTS . A PILOT STUDY 53 Yu-Ling Lee EVALUATION OF PHYSIOLOGICAL RESPONSE ON TABLE TENNIS MULTIBALL TRAINING WITH DIFFERENT LOADS 53 Irene R. Faber, Goran Munivrana, Johan Pion, Niels Faber, Maria W.G. Nijhuis-Van der Sanden DOES A PERCEPTUO-MOTOR SKILLS ASSESSMENT HAVE ADDED VALUE FOR TALENT DETECTION IN TABLE TENNIS? 54 Isao Hayashi, Honoka Irie, Toshiyuki Maeda, Masanori Fujii, Tokio Tasaka VISUALIZATION OF TABLE TENNIS SKILL BY NEURAL NETWORKS AND FUZZY INFERENCE 54 Sean Picton Doherty, Guillaume Martinent, Amanda Martindale, Irene R. Faber DETERMINANTS FOR TABLE TENNIS PERFORMANCE IN ELITE SCOTTISH YOUTH PLAYERS USING A MULTIDIMENSIONAL APPROACH; A PILOT STUDY 55 Akiyoshi Shioiri, Yuumi Terada, Yukihiko Ushiyama, Kei Kamijima, Ping Gao DEVELOPMENT OF SYSTEM OF TABLE TENNIS GAME ANALYSIS USING ULTRASONIC SENSOR 55 Cheng-Hua Huang, Ming-Cheng Kuo, Li-hua Lin, Liang-Chun Wang A COMPARATIVE STUDY OF THE STATISTICS OF TABLE TENNIS SINGLES MATCHES IN RIO 2016 OLYMPICS 56 Ziwei Cao, Yi Xiao EXPERIMENTAL STUDY ON IMPROVING THE STRIKING EFFECT OF JUVENILE TABLE TENNIS PLAYER`S FOREHAND LOOP BY BARE-HANDED WEIGHT TRAINING 56 Yan Lin, Xiaohui Tang, Changrui Liu, Yingqiu Zhang THE EFFECT OF IMPLEMENTING PLASTIC BALL IN CHINESE EXCELLENT FEMALE TABLE TENNIS PLAYERS` TECHNIQUE AND TACTICS PERFORMANCES 57 Higinio González-García, Antonia Pelegrín Muñoz DIFFERENCES IN PSYCHOLOGICAL SKILLS IN TABLE TENNIS PLAYERS DEPENDING ON SPORT LEVEL 57 Kebing Jiang, Zhihao Shi RESEARCH ON THE INTERNATIONAL PROMOTION ROUTE OF TABLE TENNIS - A CASE STUDY OF CTTC 58 Ming-Yueh Wang, Chi-Yueh Hsu, Yu-Hsin Yi, Ci-Jhan He COMPETITION TACTIC APP DEVELOPMENT OF TABLE TENNIS PLAYER 58 Jerzy Grycan FUNDAMENTAL STAGE OF DEVELOPMENT IN TABLE TENNIS (POLISH EXPERIENCE) 59 Dandan Xiao, Yingqiu Zhang, Xiaopeng Zhang, Fengde Liu THE STUDY ON THE ORNAMENTAL EFFECT OF THE COLORED PLASTIC TABLE TENNIS 59 Cheng-Hua Huang, Ming-Cheng Kuo, Li-hua Lin, Liang-Chun Wang A STUDY ON THE TECHNIQUE AND TACTICS OF WHEELCHAIR TABLE TENNIS MEN`S DOUBLES 60 Higinio González-García, Antonia Pelegrín Muñoz MOTIVATION DIFFERENCES IN TABLE TENNIS PLAYERS DEPENDING ON AGE 60 Jie Peng THE DISCUSSION HOLD TO CLAP TO SEPARATE`NET TO RESIST THE SPORT TECHNICAL ABILITY IN THE ITEM (TABLE TENNIS, BADMINTON, TENNIS) OF SKILLS MIGRATION 61 Kangkang Zhou, Zhuhang Huang, lu Zhang, Xiong Wang, Chen Luo, Zhaozhe Shen ROC AND DICRIMINANT ANALYSIS CAN PREDICT INJURIES BY THE FUNCTIONAL MOVEMENT SCREEN IN THE CHINESE HIGH-LEVEL TABLE TENNIS ATHLETES 62 Wenwen Huang, Zhihao Shi, Jie Ren THE INTELLIGENT ANALYSIS SYSTEM FOR TABLE TENNIS TECHNIQUES AND TACTICS AND ITS APPLICATION IN 2016 RIO OLYMPICS 63 Caiyan Guo, Tuoheng Li RESEARCH ON THE CURRENT SITUATION AND DEVELOPMENT STRATEGY OF CHINA TABLE TENNIS SUPER LEAGUE 64